CONECTE: atualização de medida psicométrica e construção/avaliação de um programa de treinamento de habilidades sociais conjugais para casais de diferentes orientações sexuais - Cardoso, Bruno Luiz Avelino (2021)
Couples’ Social Skills (CSS) are classes of behaviors that function to maximize couples’ satisfaction, increase the quality of the relationship, and reduce problems in the relationship. These behaviors (CSS) can be developed through specific programs, whose results show effectiveness in studies abroad. However, Brazilian research on this topic has been predominantly focused on characterization and correlation (not intervention) with heterosexual married couples. Such research was driven by the creation of the only instrument available in Brazil to measure CSS, the Couples’ Social Skills Inventory (CSSI-Villa&Del-Prette), which lacks psychometric refinement. This thesis had as main objectives: (1) to update the norms of the CSSI-Villa&Del-Prette for same-sex couples and (2) to build/evaluate a Couples’ Social Skills Training Program (CONECTE) for couples of different sexual orientations. For this, in Study 1, it was possible to discuss preliminary theoretical aspects for an intervention in CSS focused on sexual diversity and gender. In Study 2, the conceptual basis of the field of Social Skills Training and multimodal methods of evaluating CSS was presented. In Study 3, it was possible to estimate new psychometric evidence for the CSSI-Villa&Del-Prette, assess the model’s invariance as a function of gender and sexual orientation, and characterize and identify specificities of the CSS repertoire in relation to gender and sexual orientation. Exploratory structural equation modeling and polychoric correlation matrices were used, in addition to analyzes using the t-Student test and MANOVA. The invariance of the CSSI-Villa&Del-Prette was verified regarding gender and sexual orientation. However, same-sex couples had higher means for the total CSS repertoire and in the subclasses Assertive Reciprocity, Assertive Self-affirmation, and Affection/Empathy. In these same variables, women had higher means than men. In Study 4, the effects of the CONECTE program, in the online modality, with heterosexual couples and same-sex couples were tested through an experimental design. Fifteen cisgender couples (n=30), allocated into experimental (EG) and control (CG) groups, answered the CSSI-Villa&Del-Prette, Couples’ Quality Scale and Couples’ Satisfaction Scale in the pre- and post-test evaluation. Descriptive and inferential statistical analyzes were used for data analysis, including the Shapiro-Wilk, t-Student and Generalized Estimating Equations tests. Statistically significant changes were found between the pre- and post-test of the EG, for indicators of CSC, Couples’ Quality and Couples’ Satisfaction, as they did not occur in the CG. An intriguing fact was observed for the level of dissatisfaction regarding the structural aspects of the relationship, which was increased both for the CG and for the EG, especially considering the EG of Heterosexual couples. The results obtained in these studies are pioneering in Brazilian literature, especially in the approach to couples with different sexual orientations, the proposal of multimodal assessment for couples and the novelty of a Brazilian program for couples in the online modality. It is expected that the results found in this thesis will guide further research and expand the possibilities for studies in the field.